Considering sex/gender in interventions to promote children’s and adolescents’ leisure-time physical activity: a systematic review and meta-analysis - Schulze, Carolin; Bucksch, Jens; Demetriou, Yolanda; Emmerling, Sandra; Linder, Stephanie; Reimers, Anne Kerstin (Journal of Public Health, 2021)
Aim The main objectives of this systematic review were to evaluate the effects of interventions on leisure-time PA of boys and girls and to appraise the extent to which studies have taken sex/gender into account. Subject and methods PRISMA guidelines were followed. Two researchers independently screened studies for eligibility and assessed the risk of bias. Descriptive analyses were conducted to evaluate intervention effects in relation to the consideration of sex/gender in the studies based on a newly developed checklist. Additionally, meta-analyses were performed to determine the effect of interventions on girls’ and boys’ leisure-time PA. Results Overall 31 unique studies reported 44 outcomes on leisure-time PA and 20,088 participants were included in the current study. Consideration of sex/gender aspects in studies is low. PA outcomes with statistically significant same/similar effects in boys and girls showed higher quality of reporting sex/gender aspects of theoretical and/or conceptual linkages with sex/gender, measurement instruments, intervention delivery, location and interventionists and participant flow than PA outcomes without significant effects in both boys and girls or effects only in boys or girls. Interventions had a small but significant effect on girls (number of included studies (k) = 9, g = 0.220, p = .003) and boys (k = 7, g = 0.193, p = .020) leisure-time PA. Conclusion Higher reporting of sex/gender aspects may improve leisure-time PA of boys and girls. Nevertheless, there remains a need to address sufficient consideration of sex/gender aspects in interventions in the context of PA.
Keywords: Sport; Exercise; Boys; Girls; Health; Equity